Refining the Morning Covey-Call Survey to Estimate Northern Bobwhite Abundance - Joshua P. Rusk; Jason L. Scott; Fidel Hernandez; Fred C. Bryant (National Quail Symposium Proceedings, 2017)
Morning covey-call surveys have been mentioned extensively as a practical and efficient way to estimate abundance of northern bobwhite (Colinus virginianus) with minimal effort. However, many of the protocol specifics such as radius of audibility and probability of a covey calling were not based on empirical data. Other limitations also existed such as variation in observers’ detection capacity and calling behavior of coveys. These shortcomings limit the reliability of this survey technique. The objectives of our study were to 1) obtain an empirical estimate of radius of audibility, 2) document observer variability in estimating number of coveys heard, and 3) document calling behavior of bobwhite coveys. We found no difference in radius of audibility for areas with low-brush density (6%; 956 ± 72m; mean ± SE; n = 4 observers) and high-brush density (30%; 931 ± 66 m). We calculated an overall radius of audibility of 900 m (254 ha) pooled across sites. We documented considerable observer variability (CV 18-49%; n = 12 observers) in detecting coveys. Regarding calling behavior, we observed that 67% ± 9.0 (n = 30 coveys) of coveys emitted the covey-call during 2004 whereas 88% ± 7.8 (n = 17 coveys) of coveys emitted the covey-call during 2005. Of the coveys that called, 70% ± 10.2 in 2004 and 93% ± 6.4 in 2005 involved >1 bird calling/covey. Our findings allow for a refinement of the morning covey-call survey. We recommend obtaining site-specific radius of audibility and using a core number of observers that remain consistent from year to year.
Keywords: morning covey call; northern bobwhite; radius of audibility; survey